“Coping with School Bullying”: A prevention supportive program for secondary school students - Ρούση - Βέργου Χριστίνα; Ανδρέου Ελένη; Διδασκάλου Ελένη (Psychology: the Journal of the Hellenic Psychological Society, 2019)
The aim of the paper is to present the outcomes of an intervention program focusing on students’ training in coping with school bullying. The moto of the program was: “Stay calm / think clearly”. The activities of the intervention program were developed at Flinders University in Australia and included: a) a DVD with four short films dealing with social exclusion, physical bullying, verbal bullying and cyber bullying, b) a workbook (for each student), c) worksheets for students and d) teachers’ instructions/feedback sheets. For the Greek adaptation of the program, a pilot study was initially conducted which led to the final implementation and evaluation of the program. The final study included 932 students derived from 14 schools in Thessaly (12 schools in the intervention group and 2 in the control group). During the repeated (three times) measures approach, we evaluated students’ self-reports concerning: a) frequency of exposure to bullying, b) perceived self-safety from school bullying, and c) perceived self-efficacy in coping with school bullying. After the implementation of the program, the seriously victimized students (around 10% of the participants) reported less incidents of victimization, while their perceived sense of safety at school was increased. Overall the findings from this study suggest that the implementation of anti-interventions of this type can play an important role in empowering adolescents to adopt effective strategies to address the negative effects associated with bullying at school.